Acute and Subchronic Toxicity Of Temu Tis (Curcuma purpurascens) Rhizome in White Rat(Rattus norvegicus) - Suprihatin Suprihatin; Carles Tambunan; Ernawati Sinaga (Universitas Nasional Jakarta, 2020)
Temu tis (Curcuma purpurascens BI) is a species of Curcuma that has not been widely studied. Although it is not very well known, temu tis is also used as a traditional medicine to treat coughs, stomach aches, and skin infections. The results of several studies proved that temu tis rhizome extract has bioactivity as an antioxidant and anti-cancer. Temu tis is also proven to contain flavonoids, terpenoids, triterpenoids, steroids, and essential oils. Because it contains bioactive substances, it is estimated that temu tis rhizome extract has the potential to be used as a medicine, therefore its safety needs to be tested. In this study, an acute and subchronic toxicity test was conducted for the ethanol extract of temu tis rhizome which was given orally to white mouse (Rattus norvegicus) using various increased doses to see the toxic effects, both qualitative and quantitative, and subchronic effects in an increase of serum level measurements for both serum glutamic pyruvic transaminase (SGPT) and serum glutamic oxaloacetic transaminase (SGOT). From the results, there was no visible toxic effect and mortality of mouse in the doses tested, namely between 1250-5000 mg/Kg body weight with the administration for 14 days. From the calculation results, the LD50 value of temu tis rhizome extract is greater than 5000 mg/Kg body weight, so it is classified into category 5 or non-toxic according to the Globally Harmonized System of Classification (GHS). Subchronic toxicity test results also showed that the administration of temu tis extract for 28 days in a dose range of 1,250-5,000 mg /Kg body weight did not significantly affect the activity of the SGOT and SGPT enzymes in the experimental mouse.